Development and evaluation of a novel Campylobacter spp. enrichment medium - Al, Serhat; Incili, Gokhan Kursad; Akcay, Aytac; Koluman, Ahmet (Elsevier, 2019)
Although rapid detection kits continue to be developed and used, the classical culture method is still accepted as a gold standard. Therefore accelerating the classical culture methods safely is important for the detection of Campylobacter. The aim of this study is to design and compare a novel developed medium with other confirmed media in naturally and experimentally contaminated food matrices. Besides classical culture methods, it is subjected to qPCR and FISH methods. In this study, Campylobacter counts are investigated in spiked milk, chicken breast meat, cumin, minced beef meat, celery and tomato puree. Also to evaluate the enrichment medium in naturally contaminated samples, Campylobacter detection is performed in 20 chicken neck skin samples obtained from different sales points. The study showed that the novel broth provides a faster detectable number of Campylobacter. It was found to provide detectable Campylobacter counts after eight hours of inoculation. The results have shown that there is a significant increase on Campylobacter count in the detection performed using the spiked foods. Furthermore, the entire natural contaminated chicken neck skin samples are found to be positive the same as the other mediums. As a result of the study, in the classic culture methods, designed enrichment medium is faster than the currently used enrichment mediums. It is an important point of view to develop fast and reliable diagnostic methods for assuring adequate public health.
Keywords: Campylobacter; Enrichment medium; Food matrices